Next generation corrosion protection for the automotive industry - Hosking, Niamh C. (2008)
Vehicle bodies are generally constructed from galvanized steel, which, together with phosphate and e-coat paint treatments, ensures corrosion resistance. The use of these materials alone cannot provide adequate corrosion protection to certain features that are inherent to vehicle body construction but are also vulnerable to corrosion, such as cut edges of panels and creviced joints. The use of further corrosion protection measures, (e.g. sealers, lacquers and waxes), is undesirable because they require additional manufacturing processes, increase weight and reduce recyclability of the vehicle. The potential benefits of using zinc-magnesium alloy coated steel (ZMG) as a substitute for conventional galvanized steel were investigated in this work. Cyclic corrosion testing in sodium chloride and acid rain-based environments was conducted on panels of ZMG and conventional galvanized steel and the resistance of each material to red rust initiation and propagation was assessed. ZMG offered approximately a 3-fold improvement in red rust resistance compared to galvanized steel in the sodium chloride test but ZMG's corrosion benefit was attenuated in the acid rain environment. Cyclic corrosion testing was also conducted on painted test panels incorporating geometric features; enhanced edge and crevice corrosion resistance was also observed for panels constructed from ZMG. Corrosion products formed in each environment were characterized using a suite of analysis techniques and mechanisms to explain the enhanced corrosion resistance of ZMG were proposed based on these products and on the literature. An inhibiting corrosion protection mechanism was suggested for ZMG whereby cathodic activity was retarded via the precipitation of insulating, sparingly soluble magnesium hydroxide. Further inhibition of cathodic activity has been attributed to the specific oxide layer (possibly magnesium oxyhydroxide doped with zinc) present at the ZMG surface. The observed efficacy of the corrosion protection mechanisms suggests that ZMG may allow improvement of the vehicle body corrosion protection system for vehicle weight and recyclability targets.